Energy-efficient sampling and transmission scheme in wireless multimedia sensor networks - SHA Chao1; SUN Li-juan1; WANG Ru-chuan1; HUANG Hai-ping1 (Tongxin xuebao)
An energy-efficient data sampling and transmission method in wireless multimedia sensor networks was proposed.Node’s sensing direction could be adjusted with the help of Voronoi diagram which enhances network coverage level.And energy consumption on sampling was reduced on the basis of periodical sleeping as well as different sampling granularities.Moreover,the transmission overhead was further brought down by means of color block matching.Simulation results show that this method obtains satisfactory performance on prolonging networks lifetime.